DIFFERENT STYLE OF COLOR: विभिन्न शैली गत वर्ण विधान - Kumar, Vipin (International Journal of Research -GRANTHAALAYAH, 2014)
While drawing, the artist takes care of what colors should be applied as per the theme. The color used in miniatures is mostly vivid. Most of the mineral colors have been used in Rajasthani, Jain and Pal style paintings. The reason for this is the unavailability of the then colors. Dark blue, red and yellow colors are used extensively in paintings. The color of Rajasthani paintings is bright and vivid in color. Because this picture is free from external effects due to less means of movement. The Mughal-style paintings show a soft-colored pattern of Persia. The relative color of Rajasthani is less bright. Appropriate colors have been used in textile ornaments. Different colors have been used in Jama, Patka, Pajama and Turban. चित्र बनाते समय कलाकार इस बात का ध्यान रखता है कि विषयानुरूप कौन से रंग लगाने चाहिये। लघु चित्रों में प्रयुक्त रंग अधिकांशतः चटकीले है। राजस्थानी, जैन तथा पाल शैली के चित्रों में अधिकांश खनिज रंगो का प्रयोग किया गया है। इसका कारण तत्कालीन रंगो की अपलब्धि भी हैै। गहरे नीले, लाल और पीले रंगो का प्रयोग चित्रों में बहुतायत से मिलता है। राजस्थानी चित्रों की वर्णिका शोख और चटकीले रंगो की है। क्योंकि आवागमन के साधन कम होने की वजह से ये चित्र वाह्य प्रभाव से मुक्त है। मुगल शैली के चित्रों में फारस की कोमल रंगो वाली पद्वति दिखाई देती है। राजस्थानी की आपेक्षा रंगो में चटकीलापन कम है। वस्त्रों आभूषणों में उचित रंगो का प्रयोग किया गया है। जामा, पटका, पाजामा और पगड़ी में भिन्न-भिन्न रंग प्रयोग किये गये है।